Modeling and Fabrication of Smart Robotic Wheelchair Instructed by Head Gesture - Muhammad Mudassir; Anas Mujahid (IAES Indonesian Section, 2021)
The confronting problem faced by the handicapped, paralyzed, disabled, and quadriplegic people is their independent mobility. They need external assistance to perform their daily life activities. This paper aims to solve that problem by smart designing and deployment of the robotic wheelchair for those who cannot perform their voluntary activities and movements. The proposed automated wheelchair comprises two parts; the first part is the user's helmet that works as a master device, and the second part is a slave device, a smart wheelchair. The master device consists of an accelerometer, microcontroller, and wireless transmitter, in which the Accelerometer recognizes the movements of the user's head and transmits the signal according to the tiltation of the user's head. Besides this, the slave device consists of a wireless receiver, microcontroller, Gyroscope, power MOSFETs, and DC geared motors mounted on a smart wheelchair, which response as per the instructions of the master device. Furthermore, the paper also provides a brief construction of this mechatronic and amphibian system using static and dynamic equations.